Suicidal Ideations and Attempts Among Adolescents in Kampala Urban Settlements in Uganda: A Case Study of Adolescents Receiving Care From the Uganda Youth Development Link - Bukuluki, Paul; Wandiembe, Symon; Kisaakye, Peter; Besigwa, Samuel; Kasirye, Rogers (Frontiers in Sociology, 2021)
There is an increasing recognition that suicidal ideation is a major public health concern in sub-Saharan Africa. We employed a case study design, taking a case study of adolescents currently under the care of Uganda Youth Development Link (UYDEL). The data analyzed were collected from 219 female and male adolescents (13–19 years) recruited through UYDEL in Kampala, Uganda. A Poisson regression model with robust variance was used to assess the risk factors associated with suicidality. The prevalence of suicidal ideation in the past 4 weeks and attempt within the past 6 months among adolescents was 30.6% (95% CI: 24.8, 38.0%) and 24.2% (95% CI: 18.7, 30.4%), respectively. The most stressful precursors of suicidal ideation or attempt included financial difficulties (59.5%), family breakdown or conflicts (37.4%), and trauma (23.1%). Suicidal ideation in the past 1 week preceding the survey was as high as 13.3% (95% CI: 9.0, 18.6%), of which 75.0% (95% CI: 55.1%, 89.3%) had a suicide plan. Prevalence of suicidal ideation in the past 4 weeks was significantly higher among respondents with moderate psychological distress [Prevalence Ratio (PRR) = 2.74; 95% CI: 0.96, 7.84] and severe psychological distress (PRR = 4.75; 95% CI: 1.72, 13.08) but lower among adolescents who knew where to obtain professional psychological care (PRR = 0.51; 95% CI: 0.30, 0.87). Similarly, suicidal attempt was significantly higher among respondents with moderate psychological distress (PRR = 4.72; 95% CI: 1.01, 12.03) and severe psychological distress (PRR = 11.8; 95% CI: 4.66, 32.37), and who abuse drugs or substances (PRR = 2.13; 95% CI: 1.13, 4.01). Therefore, suicidal ideation is a major public health issue among adolescents living in poor urban settlements in Kampala, Uganda. Psychological distress due to financial difficulties, unemployment, and family breakdown are major facilitators of suicidality among adolescents in urban poor settlements in Kampala. Interventions aimed at preventing suicide among vulnerable adolescents in urban settlements in Kampala, Uganda should incorporate this unique risk factor profile.